Circulating CD40 ligand, Dickkopf‐1 and P‐selectin in HIV‐infected patients. Issue 10 (19th August 2019) - Falasca, K; Reale, M; Di Nicola, M; Ucciferri, C; Zecca, IA; Santilli, F; Pontolillo, M; Liani, R; D'Angelo, C; Costantini, E; Vecchiet, J
Abstract : Objectives: The aim of this study was to evaluate the circulating levels of CD40 ligand (CD40 L), Dickkopf‐1 (DKK‐1) and P‐selectin, their relationships and their contributions to cardiovascular risk in subjects with HIV infection. Methods: The study population included 80 HIV‐infected patients, 14 (17.5%) of whom had diabetes mellitus (DM) and 32 (40.0%) of whom had arterial hypertension (AH). The HIV‐infected patients were compared with a control group with similar demographic and clinical features. CD40L, DKK‐1 and P‐selectin levels were measured using an enzyme‐linked immunosorbent assay. Results: The HIV‐infected patients showed higher levels of all the cardiovascular disease (CVD) markers. Both serum CD40L and DKK‐1 were significantly higher in HIV‐infected patients than in the HIV‐negative controls (P < 0.001), while soluble P‐selectin showed no significant between‐group difference (P = 0.133), reflecting the role of HIV infection in CVD. In the HIV‐infected group, patients with DM showed lower levels of CD40L and DKK‐1 in comparison with the nondiabetic patients and patients with AH (P < 0.05, with Bonferroni correction). In contrast, patients with AH showed higher levels of CD40L and DKK‐1 in comparison to patients without DM or AH ( P  < 0.05, with Bonferroni correction). Patients with AH showed higher levels of CD40L and DKK‐1 than patients with DM (P < 0.05, with Bonferroni correction). Conclusions: In this study, we found that HIV‐infected patients displayed significantly higher circulating levels of both CD40L and DKK‐1, which were linearly and directly correlated, when compared to HIV‐negative patients. The presence of diabetes was associated with lower levels of both CD40L and DKK‐1, whereas the presence of hypertension was associated with higher levels of CD40L.